The relationship between midwifery students' attitudes towards couples' sexual relationships and their clinical skills in providing sexual health of counseling services - Talaat Khadivzadeh; Mina Ardaghi; khadijeh Mirzaii; Seyyed Reza Mazloum; Esmat Modaresi (Mashhad University of Medical Sciences, 2016)
Background & aim: Midwives have a substantial role in evaluating and improving sexual health and providing family counseling. The aim of this study was to evaluate clinical skills of midwifery students of Mashhad University of Medical Sciences in providing sexual health counseling services and determine their attitudes toward sexual relations of couples in the academic year of 2014-2015. Methods:This cross-sectional study was performed on 63 midwifery students, who were selected by convenience sampling. The data collection tools included an academic and demographic questionnaire, the questionnaire of attitudes toward couples' sexual relations, and a checklist to assess the midwifery students' clinical skills in taking sexual history, providing sexual counseling during pregnancy and menopause, and diagnosis and treatment of sexual dysfunction. The checklist was completed by observers in objective structured clinical test consisting of five stations. Data analysis was performed using descriptive statistics, One-way ANOVA, Pearson correlation, repeated measures ANOVA, and regression, using SPSS version 16. Results: The mean score of students' attitude was 34.1±4.0 out of 40, and 85.7% of the participants had a very good attitude toward sexual relation of couples. The mean total score of the students' clinical skill was 22.6±8.0 out of 128, and 90.5% of the samples were at a poor level. Conclusion: Although providing sexual health counseling services is among the educational purposes of midwifery students and is one of the qualifications midwifery students and midwives must have, midwifery students' do not have satisfactory skills in this area. However, given the positive attitude of the students toward this issue, these skills can be promoted. Therefore, it is recommended to design and implement sexual health programs for midwifery students.